2016
DOI: 10.1007/s10495-016-1252-3
|View full text |Cite
|
Sign up to set email alerts
|

Detergent sclerosants at sub-lytic concentrations induce endothelial cell apoptosis through a caspase dependent pathway

Abstract: To investigate the apoptotic effects of detergent sclerosants sodium tetradecylsulphate (STS) and polidocanol (POL) on endothelial cells at sub-lytic concentrations. Human umbilical vein endothelial cells (HUVECs) were isolated and labelled with antibodies to assess for apoptosis and examined with confocal microscopy and flow cytometry. Isolated HUVECs viability was assessed using propidium iodide staining. Early apoptosis was determined by increased phosphatidylserine exposure by lactadherin binding. Caspase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Then, apoptosomes activate caspase 9 and initiate the chain reaction of caspase cascade. These processes are defined as caspase dependent-apoptosis50. On the other hand, AIF and Endo G are released from perforated mitochondria, translocated into the nucleus and induce chromosomal DNA fragmentations.…”
Section: Discussionmentioning
confidence: 99%
“…Then, apoptosomes activate caspase 9 and initiate the chain reaction of caspase cascade. These processes are defined as caspase dependent-apoptosis50. On the other hand, AIF and Endo G are released from perforated mitochondria, translocated into the nucleus and induce chromosomal DNA fragmentations.…”
Section: Discussionmentioning
confidence: 99%
“…Note: Side effects from sclerosants at doses used in varicose veins and arteries (30–150 mg/dose) include: hypersensitivity, arterial and venous thrombosis, cardiac arrhythmias, visual/neurological disturbances and skin ulcerations 23. Differences in strength have known differences in effects 24–26. We have occasionally seen a rash, but we have not seen the rest of these side effects at this clinic with the low-dose (1.1–2.5 mg) treatments.…”
Section: Resultsmentioning
confidence: 87%
“…In a number of recent in vitro studies, this group has demonstrated that detergent sclerosants induce endothelial activation, apoptosis and release of inflammatory and angiogenic cytokines at low concentrations. 20,21 Treating the telangiectasias without treating the underlying veins may result in inflammation and subsequent angiogenesis and formation of TM. This can follow sclerotherapy, endovenous laser therapy, and even venous surgery.…”
Section: Discussionmentioning
confidence: 99%